Parental democratic communication and adolescent well-being in an era of loneliness: the mediating role of societal trust - Liu, Simin; Hu, Sydney X.; Su, Lanxin (Frontiers in Psychiatry, 2024)
BackgroundIn an era marked by increasing loneliness, understanding the impact of parenting practices on adolescent well-being and resilience is crucial. This study investigates the relationship between parental democratic communication and key indicators of adolescent adjustment and well-being in China, with a focus on the mediating role of societal trust.ObjectiveThe study aimed to examine the direct effects of parental democratic communication on Chinese adolescents’ subjective well-being and to explore the mediating roles of societal trust in this relationship.MethodsData were collected from 691 high school students as part of the 2020 Chinese Family Panel Studies (CFPS). The sample was divided into two age groups: 16-17 years old (n=493) and 18 years old (n=198). Multi-group Structural Equation Modeling (SEM) was used to analyze the data.ResultsSEM analysis revealed age-specific effects of parental democratic communication (PDC) on subjective well-being (SWB). For ages 16-17, PDC directly influenced SWB (β=0.269, p<0.001) with significant serial mediations through societal trust, negative emotion, and pleasant life experiences. For 18-year-olds, only societal trust mediated the PDC-SWB relationship (β=0.16, p<0.01). Meanwhile, the effect of societal trust is superior to that of other mediating variables in both groups. Multi-group analysis showed measurement invariance but differences in structural relationships across age groups.ConclusionsParental democratic communication has a direct as well as serial mediated impact on mid-adolescents’ subjective well-being and an indirect impact through societal trust in late adolescence, among Chinese adolescents. These results point to a pattern we term “Societal Trust-Mediated Well-Being,” which appears to wield greater influence than negative emotions or pleasant life experiences, particularly among older adolescents. These results underscore the need for developmentally tailored approaches and integrative interventions that adapt to the changing dynamics of adolescent well-being in a rapidly evolving society.